Synergistic Effects of Thymoquinone and Carob Powder versus Dexamethasone in the Model of Asthma in Pregnant Rats: New Insights into their Therapeutic Effects - Ameerah Fadhil Ahmed; Şule Coşkun Cevher; Emine Gülceri Güleç Peker; Barbaros Balabanlı; Meral Ebegil (Gazi Medical Journal)
Objective: When asthma and pregnancy coexist, the mother may be severely affected. One of the main reasons for this situation is that it is positively correlated with especially increased oxidative stress due to the co-occurrence of asthma and pregnancy. Even pregnancy alone increases oxidative stress in the body, and with the addition of asthma, an increased chain of events is added. In this sense, diet and nutrition styles can be considered as factors that regulate both events in a controlled way. Increasing anti-oxidant intake in the diet can play a leading role in eliminating the increased Reactive oxygen species; thus, this negative effect in asthma and pregnancy can be alleviated. Studies on the protective role of antioxidants in asthma are limited, but not few. The aim of this study was to reveal the strength of the effects of thymoquinone (TQ) and carob powder administration, which are known to have two different strong antioxidant effects during pregnancy, on the oxidative event in the mother with the diet management strategies. Methods: In this study, it was tried to improve the asthmatic pregnant rat and to determine the direction of oxidant-antioxidant balance with a holistic antioxidant complex Female rats were divided into 3 groups: asthmatic pregnant group (1) sensitized via an intraperitoneal injection of ovalbumin (OVA) with alum on days 0 and 14 and exposed to aerosolized OVA 3 days over the subsequent 1 week then coupled with male rats to get pregnant; asthmatic pregnant with TQ and carob (CS) group (2) sensitized as above then administered each of TQ and CS on the last 5 days of pregnancy; and asthmatic pregnant with dexamethasone group (3) sensitized as above then received dexamethasone by intraperitoneal injection on last 5 days of pregnancy. Results: The co-administration of TQ and CS decreased malondialdehyde levels, increased nitric oxide, ascorbic acid, and glutathione levels in lung tissue. In addition, the levels of some proinflammatory cytokines were decreased in the serum. The cumulative protective effects of TQ and CS were successful in reducing inflammation in the lungs. Conclusion: The administration of TQ and CS may be considered as a candidate for a new herbal blend or adjuvant for asthmatic pregnant, given the side effects of cortisol.